Measuring urban sprawls on highway strips parameters using GIS approach - zainab, Khin Cho Myint; Hj. Mohd. Noor, Norzailawati (2012)
Urban sprawl has increasingly become a major issue in the global trend towards urbanization. It has become a common problem, and is being faced by both developed and developing countries nowadays. It is refers to a specific form of urban development characterized by low-density, leapfrog, commercial strip development and discontinuity ((Ewing, 1997; Downs 1999; Galster et al., 2001; Malpezzi and Guo, 2001)Most of the urban sprawl is considered to be the expansion of low density accompanied by a series of environmental and socio-economic issues. Furthermore, the important characteristics of sprawl include unlimited outward extension of development, dominance of transportation by private automobiles, fragmentation of land use, and large fiscal disparities among individual communities (Burchell 1998). According to Ewing (1997), these features accelerate the spatial expansion of metropolitan areas by creating discontinuous land use patterns. Many studies have shown that sprawl is more expensive than an alternative pattern of development .It is not immediately apparent how all the series of characteristics or attributes can be measured. Over the last decade, there has been a rapid increase in the amount of literature on the measurement of urban sprawl. This is because urban sprawl, which encompasses multiple aspects of urban spatial development, has been one of the debatable discussions in the field of urban and regional planning. However, the factors influencing the development of sprawl are multifaceted and include rapid urbanization, agricultural, industrialization, migration, economic development, income growth, development policy, market failures and population growth. Thus the issue of sprawl is become preference nowadays. Therefore, this paper endeavour to analyze and measuring urban landuse sprawl at residential, industrial and commercial based on determination of spatial factor especially on leapfrog parameter using GIS approach.